The practical guide to keeping chickens, ducks, geese, & turkeys : a directory of poultry breeds and how to keep them - Hams, Fred, author (Leicestershire [England] : Lorenz, 2012)
Discusses what features to look for when purchasing poultry and provides information on feeding, hygiene, treating illness, and good husbandry practices